THE WORKFORCE QUALITY OF ASEAN ECONOMIC COMMUNITY: CASE IN INDONESIA - Nusraningrum, Dewi; Dores, Ardiansyah (Universitas Mercu Buana, 2018)
The composition of the Indonesia’s workforce is still dominated by Elementary and secondary school graduate. This study aimed at mapping the Quality of Workforce Education toward Asean Economic Community is a case study in the research area of West Jakarta. Long-term Objectives: To identify the progression of the quality of workforce education in West Jakarta, forecasting inventory and employment needs of West Jakarta, and formulate policies and programs necessary workforce advancement. The results of the study with a descriptive method of analysis indicate the need for: improving the quality of workforce education to conform to the Mutual Recognition Arrangements (MRAs) for major professional services of the Asean Economic Community, identifying the level of inventory and employment needs of West Jakarta, encourage absorption of the workforce, the Government of West Jakarta, to formulate policies and programs of workforce according to Mutual Recognition Arrangements (MRAs) for major professional services in Asean Economic community